Isolation and immunomodulatory activity of bursal peptide, a novel bursal peptide from the chicken bursa of Fabricius - Liu, Xiao-Dong (J Vet Sci, 2015)
The bursa of Fabricius (BF), which is unique to birds, serves as the central humoral immune organ and plays a significant role in B lymphocyte differentiation. In this study, a new bursal peptide (BP-IV) was isolated from BF, which promoted colony-forming unit pre-B formation and regulated B cell differentiation. BP-IV also exerted immunomodulatory effects on antigen-specific immune responses via both humoral and cellular immunity in chicken and mice that had been immunized with inactivated avian influenza virus (AIV; H9N2 subtype), including enhancing AIV-specific antibody and cytokine production. The results of this study provided novel insights into the use of a potential candidate reagent for B cell development and future immuno-pharmacological use.